An Economic Analysis of Examination Malpractice in Senior Secondary Schools: A Principal-Agent and Rent-Seeking Perspective Based on the Lived Experiences of Quality Assurance Leaders in Northwestern Nigeria - Chukwuebuka, Chukwuebuka (PERFECT EDUCATION FAIRY, 2024)
Examination malpractice is a persistent phenomenon that undermines the integrity of the educational system and labor market in Nigeria, representing a form of market failure in signaling human capital quality. This phenomenological qualitative study analyzes the lived experiences of nine quality assurance leaders responsible for monitoring the Senior Secondary Certificate Examination (SSCE) in Northwestern Nigeria. Through in-depth interviews and thematic analysis, the study identifies malpractice mechanisms as opportunistic behaviors driven by economic incentives and social pressures, involving both internal and external agents within a principal-agent problem framework. Findings suggest that malpractice represents rent-seeking behavior triggered by the overemphasis on certificates as labor market signals (signaling theory), exacerbated by infrastructural deficiencies that increase compliance costs. The study recommends policy interventions focused on restructuring incentive systems through stronger legal enforcement, leveraging technology to reduce information asymmetries in supervision, and shifting social focus from formal credentials to actual competencies to improve the efficiency of education and labor markets